Formation of family group names using the stem of -gaster, with special reference to names based on Miscogaster and Sphegigaster (Hymenoptera: Chalcidoidea: Pteromalidae) - Burks, Roger A. (Zootaxa, 2012)
Article 29.3.1 of the International Code of Zoological Nomenclature dictates that family group names are formed by deleting the case ending from the genitive singular, when the genus ends in a Latin or classical Greek word (ICZN 1999). This process determines the genitive stem of the word. Formation of a family group name based on an incorrect genitive stem is considered an incorrect original spelling, and the Code requires that it be be automatically changed to the correct stem if described before 1999 in cases where this does not create a junior homonym (Article 35.4.1).